(untitled) (Journal of the College of Basic Education, 2022)
Teaching aids play an important and effective role in the educational process, through which the teacher and the teacher can make his lecture a useful scientific lecture that achieves the required cognitive, skillful and emotional goals, and transfers the atmosphere of the lecture from monotony and inactivity to an atmosphere of interaction and movement, which motivates them to seek knowledge.In the history of Western education, the use of the blackboard did not spread in schools except in the nineteenth century AD, although the picture of the blackboard appeared in the book (The World as a Picture) by the educator John Amos Comenus (1670-1592) Comenus, which was published in 1653 in an attempt to teach the Latin language systematically. New, however, many of the innovations of this educator did not find their way to acceptance and popularity in Western educational systems until after a long time) (1).Since the blackboard is one of the visual aids and one of the oldest, easiest to use and most useful, I tried in this research to give a clear picture of the importance of the blackboard in teaching Arabic to foreigners.